PENGARUH MACAM AMELIORAN LOKAL DAN DOSIS LEGIN KORO TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KORO PEDANG (Canavalia ensiformis L.) DI LAHAN MARJINAL TANAH GRUMUSOL - Ismail Marjuki; Sri Endah Prasetyowati Susilaningsih; Maria Theresia Darini (JURNAL ILMIAH AGROUST, 2018)
This study aims to determine the effect of local ameliorant of types and the dosage of Legin bean on the Jack Bean plant. The research was conducted in March to July 2018 on the UPTD land in the Development of Food Crops and Horticulture Hatchery, Gading unit. Jl. Yogyakarta-Wonosari Km 33, Playen, Gading, Gunung Kidul District, Special Region of Yogyakarta, at an altitude of 200 meters above sea level and temperatures between 23-32 0C, in grumusol soil type. The study was arranged in Randomized Complete Block Design (RCBD) consisting of two factors and three replications. The first factor has the type of local ameliorant consisting of chicken manure and gamal green fertilizer. The second factor has the dose of legin koro which consists of three levels, namely: without legin koro dose, 50 g dose of legin koro, and 100 g legin koro. The observation variables included the plant height, number of leaves, production branches, plant fresh weight, plant dry weight, number of active root nodules, number of pods per plant, pod length per plant, dry pod weight per plant, weight of 100 seeds, and yield per hectare analysis. The result of the study showed no interaction between the treatment of local ameliorant and legin bean dosages on all observation variables, the type of ameliorant did not affect to plant growth, but increase the yield of seeds per hectare and the dosage of legin bean did not affect plant growth, but increase the yield of seeds per hectare